Credit Access Towards MSMEs: An Investigation of Banker's Perspectives - Nair, Greeshma S.; Gopal, Nikita (SEDME (Small Enterprises Development, Management & Extension Journal), 2024)
Micro, small and medium enterprises (MSMEs), which are business activity units that run businesses in several fields, are vital for the economies of several countries. Credit access (CA) is regarded as an important matter for MSMEs' growth in the development and sustainable growth of MSMEs. In the financial sectors, the government's role via policies like augmenting MSMEs' credit becomes completely significant. For evaluating CA towards MSMEs in Kerala, this study was developed. Analysing the challenges in accessing credit in MSMEs is the aim. For evaluating the outcomes, a simple random sampling methodology was deployed. In Kerala, the impact of credit knowledge was significant on MSMEs' CA. As per the outcomes, a greater probability of augmenting loan access is engendered by the factor of challenges in attaining private equity funding and high lending interest rate.
Keywords: Financial Sectors; Investigation of Banker's; MSMEs; Credit Access